2021
DOI: 10.1002/art.41901
|View full text |Cite
|
Sign up to set email alerts
|

Phase IIa Global Study Evaluating Rituximab for the Treatment of Pediatric Patients With Granulomatosis With Polyangiitis or Microscopic Polyangiitis

Abstract: To assess the safety, tolerability, pharmacokinetics, and efficacy of rituximab (RTX) in pediatric patients with granulomatosis with polyangiitis (GPA) or microscopic polyangiitis (MPA).Methods. The Pediatric Polyangiitis Rituximab Study was a phase IIa, international, open-label, single-arm study. During the initial 6-month remission-induction phase, patients received intravenous infusions of RTX (375 mg/m 2 body surface area) and glucocorticoids once per week for 4 weeks. During the follow-up period, patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 23 publications
1
27
0
1
Order By: Relevance
“…During the overall study period (up to 4.5 years observation), 23 patients reported 105 infections; 91% were nonserious AEs. Details of infections in PePRS have been reported previously [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…During the overall study period (up to 4.5 years observation), 23 patients reported 105 infections; 91% were nonserious AEs. Details of infections in PePRS have been reported previously [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our analysis also demonstrated that pediatric patients with GPA/MPA treated with rituximab had peripheral B-cell depletion after induction therapy, which was maintained through at least month 18. Previous exploratory analyses of pediatric patients in PePRS and adult patients in the RAVE trial demonstrated that higher rituximab exposure was correlated with longer-lasting B-cell depletion [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations